Fuzzy mud ebook - Sachar, Louis (2015)
From the author of the acclaimed bestseller Holes , winner of the Newbery Award and the National Book Award, comes a New York Times bestselling adventure about the impact we have—both good and bad—on the world we live in.    Be careful. Your next step may be your last.   Fifth grader Tamaya Dhilwaddi and seventh grader Marshall Walsh have been walking to and from Woodridge Academy together since elementary school. But their routine is disrupted when bully Chad Hilligas challenges Marshall to a fight. To avoid the conflict, Marshall takes a shortcut home through the off-limits woods. Tamaya, unaware of the reason for the detour, reluctantly follows. They soon get lost. And then they find trouble. Bigger trouble than anyone could ever have imagined.   In the days and weeks that follow, the authorities and the U.S. Senate become involved, and what they uncover might affect the future of the world.   "Sachar blends elements of mystery, suspense, and school-day life into a taut environmental cautionary tale."— Publishers Weekly